Safety and tolerability of inebilizumab (MEDI-551), an anti-CD19 monoclonal antibody, in patients with relapsing forms of multiple sclerosis: Results from a phase 1 randomised, placebo-controlled, escalating intravenous and subcutaneous dose study - Agius, Mark A (Mult Scler, 2017)
BACKGROUND: B cells may be involved in the pathophysiology of multiple sclerosis (MS). Inebilizumab (formerly MEDI-551) binds to and depletes CD19(+) B cells. OBJECTIVES: To assess safety, tolerability, pharmacokinetics, pharmacodynamics and immunogenicity of inebilizumab in adults with relapsing MS. METHODS: This phase 1 trial randomised 28 patients 3:1 (21, inebilizumab; 7, placebo) to inebilizumab (2 intravenous (IV) doses, days 1 and 15: 30, 100 or 600 mg; or single subcutaneous (SC) dose on day 1: 60 or 300 mg) or matching placebo, with follow-up until at least week 24 or return of CD19(+) B-cell count to ⩾80 cells/µL. RESULTS: Complete B-cell depletion was observed across all doses. Infusion/injection (grade 1/2) reactions occurred in 6/15 patients receiving inebilizumab IV, 2/5 placebo IV and 1/6 inebilizumab SC. Serious adverse events occurred in three patients receiving inebilizumab: pyrexia, mixed-drug intoxication (unrelated to inebilizumab; resulted in death) and urinary tract infection. Mean number of cumulative new gadolinium-enhancing lesions over 24 weeks was 0.1 with inebilizumab versus 1.3 with placebo; mean numbers of new/newly enlarging T2 lesions were 0.4 and 2.4, respectively. CONCLUSION: Inebilizumab had an acceptable safety profile in relapsing MS patients and showed a trend in reductions in new/newly enlarging and gadolinium-enhancing lesions.